(untitled) (Indonesian Court and Justice Review, 2025)
Ensuring child-friendly justice is a fundamental component of a rights-based legal system. In Indonesia, while legislative reforms—such as the Juvenile Justice System Law (Law No. 11/2012)—aim to protect children’s rights during legal proceedings, implementation gaps persist. This study evaluates the extent to which the Indonesian legal system upholds child protection principles in criminal and civil judicial processes. Drawing on case analysis, field observations in child courts, and interviews with judges, lawyers, and child protection agencies, the research assesses procedural safeguards, restorative justice practices, and institutional support for child litigants. The findings indicate that although progress has been made in establishing special courts and diverting children from detention, significant challenges remain: lack of trained personnel, inadequate victim support systems, and limited awareness among law enforcement. Furthermore, the adversarial nature of courtrooms often fails to accommodate the psychological needs of children, especially in sensitive cases like abuse or custody disputes. This study’s novelty lies in its empirical grounding and child-centered approach, offering a multidimensional evaluation of the justice system’s responsiveness to children’s rights. It contributes to the broader discussion on legal reform by emphasizing the need for systemic changes in judicial attitudes, courtroom procedures, and inter-agency coordination. The study concludes with policy recommendations aimed at strengthening child-sensitive justice in Indonesia.